The influence of gender and waist circumference in the association of body fat with cardiometabolic diseases - Milad Bagheri; Mehran Nouri; Ali Kohanmoo; Reza Homayounfar; Masoumeh Akhlaghi (BMC Nutrition)
Abstract Background The link between obesity and cardiometabolic risk has been well recognized. We investigated the association between body fat percentage (BF%), as an appropriate indicator of obesity, and prevalence of cardiometabolic diseases using baseline data of Fasa PERSIAN cohort study. Methods The cross-sectional study was performed on data obtained at the first phase of the Fasa cohort study in Iran (n = 4658: M/F: 2154/2504). Anthropometric characteristics, blood pressure, cardiometabolic biomarkers, and body fat content were measured. Information on demographic and lifestyle factors, and history of cardiometabolic diseases (metabolic syndrome, type 2 diabetes, non-alcoholic fatty liver disease (NAFLD), and myocardial infarction) was obtained. Results Cardiometabolic risk factors (body mass index, waist circumference, blood pressure, blood glucose and lipids) had an inverse association with BF% tertiles in both sexes. Women had a higher BF% and prevalence of metabolic diseases than men, but men demonstrated stronger associations between BF% and cardiometabolic diseases. In both sexes, the association between BF% and metabolic syndrome and NAFLD was stronger than that between BF% and diabetes and myocardial infarction. Addition of waist circumference to the confounders either weakened (for NAFLD and metabolic syndrome) or faded (for type 2 diabetes and myocardial infarction) the relationship of BF% and cardiometabolic diseases. Conclusion Strategies to decrease body fat may be effective in ameliorating the risk of milder metabolic diseases, such as metabolic syndrome, but interventions to decrease abdominal fat (estimated by waist circumference) may be more effective in preventing more serious metabolic disorders such as type 2 diabetes and myocardial infarction.